Clinical Efficacy of Subgingivally Delivered 1.2% Atorvastatin in Chronic Periodontitis: A Randomized Controlled Clinical Trial. Issue 7 (1st July 2013) - Pradeep, A.R.; Kumari, Minal; Rao, Nishanth S.; Martande, Santosh S.; Naik, Savitha B.
Abstract : Background: Atorvastatin (ATV) is a specific competitive inhibitor of 3‐hydroxy‐2‐methyl‐glutaryl coenzyme A reductase. Recently, statins have shown pleiotropic effects such as anti‐inflammation and bone stimulation. The aim of the present study is to investigate the effectiveness of 1.2% ATV as an adjunct to scaling and root planing (SRP) in the treatment of intrabony defects (IBDs). Methods: Sixty individuals were randomized into two treatment groups: SRP plus 1.2% ATV and SRP plus placebo gel. At baseline and 3, 6, and 9 months, clinical parameters, which included modified sulcus bleeding index, plaque index, probing depth (PD), and clinical attachment level (CAL), were recorded at baseline. Radiologic assessment of IBD fill was done using computer‐aided software at baseline and 6 and 9 months. Results: Mean PD reduction and mean CAL gain were greater in the ATV group than the placebo group at 3, 6, and 9 months. A significantly greater mean percentage of radiographic bone fill was found in the ATV group (35.49% ± 5.50%) compared to the placebo group (1.82% ± 1.32%) after 9 months. Conclusion: ATV as an adjunct to SRP can provide a new direction in the management of IBDs.